2017
DOI: 10.1088/1361-648x/aa92fe
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the reduction process of graphene oxide probed by Raman spectroscopy mapping

Abstract: We propose a method for monitoring the large-scale homogeneity of the reduction process of graphene oxide. For this purpose, a Raman mapping technique is employed to probe the evolution of the phonon properties of two different graphene oxide (GO) thin films upon controllable thermal reduction. The reduction of GO is reflected by the upshift of the statistical distribution of the relative intensity ratio of the G and D peaks (I /I) of the Raman spectra and is consistent with the ratio obtained for chemically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 49 publications
1
17
0
3
Order By: Relevance
“…The Raman map of I D /I G , Fig. 3(c) reveals a distribution of GO in the window area with a mean value of 1.23, which is within the reported range, 0.67 to 1.4 31 . However, a trace of darker colour from the map reveals the shape of the underlying ring, indicating a slightly lower I D /I G ratio close to the ring.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The Raman map of I D /I G , Fig. 3(c) reveals a distribution of GO in the window area with a mean value of 1.23, which is within the reported range, 0.67 to 1.4 31 . However, a trace of darker colour from the map reveals the shape of the underlying ring, indicating a slightly lower I D /I G ratio close to the ring.…”
Section: Resultssupporting
confidence: 71%
“…3(d) confirms this with a mean I D /I G ratio of 1.14 for the GO over the ring. Wroblewska et al previously showed that the I D /I G ratio increases as the GO undergoes thermal reduction 31 . However, the I D /I G ratio is also known to be electrically tuneable 32 , suggesting that it is influenced by localised (trapped) charges, e.g.…”
Section: Resultsmentioning
confidence: 97%
“…The G band in the Raman spectra corresponds to sp 2 hybridised carbon-based material [26]. The D peak is related to defect or lattice disorder due to the binding of oxygen-functional group [27]. The intensity of the D band is associated with the size of the sp 2 in-plane domains [26].…”
Section: Discussionmentioning
confidence: 99%
“…Two main bands were observed in the spectrum: D (1345.9 cm −1 ) and G (1590.5 cm −1 ), in which peak positions and intensity of each band were obtained from Lorentzian fitting. Based on a relative intensity ratio of the D and G modes (I D /I G = 1.20) we confirmed the purity and presence of GO on the optical fiber before covering with a thin layer of PMMA [ 26 ]. The Raman spectra were collected by using a 514 nm laser in a Renishaw inVia spectrometer in ambient conditions.…”
Section: Methodsmentioning
confidence: 64%